2008
DOI: 10.1590/s1806-83242008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of stone casts obtained by different impression materials

Abstract: Several impression materials are available in the Brazilian marketplace to be used in oral rehabilitation. The aim of this study was to compare the accuracy of different impression materials used for fixed partial dentures following the manufacturers' instructions. A master model representing a partially edentulous mandibular right hemi-arch segment whose teeth were prepared to receive full crowns was used. Custom trays were prepared with auto-polymerizing acrylic resin and impressions were performed with a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 14 publications
2
70
0
11
Order By: Relevance
“…Studies have also shown inconsistent results for irreversible hydrocolloid impressions. 46,47 Another patient-specific factor sometimes discussed is the deformation of the mandible during jaw opening. In this in vivo study, no difference was visible between the precision of maxillary and mandibular impressions in both the conventional and digital impression groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown inconsistent results for irreversible hydrocolloid impressions. 46,47 Another patient-specific factor sometimes discussed is the deformation of the mandible during jaw opening. In this in vivo study, no difference was visible between the precision of maxillary and mandibular impressions in both the conventional and digital impression groups.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study confirm the excellent dimensional stability and the reproduction of details achieved when using this material, as described previously. [11][12][13] The condensation silicone shows low resistance to rip and higher deformation than other elastomeric materials, and increased distortion when it is stored prior to pouring. The dimensional instability may be due to ethylic alcohol, which could be produced as a by-product of the chemical reaction of this silicone.…”
Section: Discussionmentioning
confidence: 99%
“…Addition silicones, mercaptanpolysulfides, and polyetheres are the most common additives for this procedure. [8][9][10][11][12][13][14][15][16][17] The thickness of the impression material, in addition to the effects of temperature and the materials used, influences the mould, producing excessive distortion of the impression. 9,10 The individual shell technique is advantageous because the thickness of the material is less and it thus produces only minor dimensional changes in the impression.…”
Section: Introductionmentioning
confidence: 99%
“…3 Alginate and gypsum are materials extensively used to make impressions and casts, respectively. 4,5 The alginate presents problems with dimensional stability over time, and water loss causes roughness on the plaster surface, therefore it is not recommended for the construction of indirect restorations. 4 However, it has been the material of choice for making orthodontic study models, Declaration.of.Interests:.The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…because it is easy to use, is well accepted by the patient, has low cost, 4,6,7 and presents adequate dimensional stability, provided that the manufacturer's instructions as regards pouring time are followed.…”
Section: Introductionmentioning
confidence: 99%